Physical properties of Physalis peruviana L - Oliveira, Solange (2016)
Physalis (Physalis peruviana L.), also known as cape gooseberry or ground-cherry, plays an important role in nutrition as an excellent base for dietetic products. Highly valued for its unique flavour, texture and colour, recent research has shown that physalis fruit is rich in many beneficial compounds. In this study, the diameter and mass of physalis fruits were measured, which can be used to calculate other biometric characteristics of the fruit, such as: surface area, volume or density. Other physical properties were measured, namely the colour coordinates, by means of a Chroma meter, whilst the textural parameters firmness and elasticity were measured with a texturometer. The following values were calculated for the physalis fruits analysed in the present work: 1.69 cm for average diameter; 8.98 cm2 for surface area, 2.51 cm3 for volume; 2.77 g for mass was, and 1.10 g/cm3 for density. The colour coordinates were 56.72 for lightness, 16.69 for redness, and 58.11 for yellowness. Skin firmness and elasticity were evaluated for texture attributes, and their average values were 2.40 N and 2.94 mm, respectively. The results of this work are in accordance